2018
DOI: 10.1186/s13287-018-1063-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficiency of human amniotic epithelial stem cell-derived functional hepatocyte-like cells in mice with acute hepatic failure

Abstract: BackgroundHepatocyte transplantation has been proposed as an effective treatment for patients with acute liver failure (ALF), but its application is limited by a severe shortage of donor livers. Human pluripotent stem cells (hPSCs) have emerged as a potential cell source for regenerative medicine. Human amniotic epithelial stem cells (hAESCs) derived from amniotic membrane have multilineage differentiation potential which makes them suitable for possible application in hepatocyte regeneration and ALF treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…Indeed, AEC have been proved capable to interact with different typologies of host damaged tissue such as lung 10 , liver 11 , cholangiocyte 12 , CNS 13 , tendon 14 or sinusoidal endothelial cells 11 by promoting regeneration, managing inflammation and replacing damaged cells with functional/mature ones (without cell fusion). The level of maturation implies either a tissue replacement as epithelial cells [15][16][17][18][19][20][21] , or as mesenchymal cells by experiencing 1 Faculty of Bioscience and Technology for Food, Agriculture and Environment, University of Teramo, Teramo, Italy.…”
Section: Epithelial-mesenchymal Transition (Emt) Is a Complex Biologimentioning
confidence: 99%
“…Indeed, AEC have been proved capable to interact with different typologies of host damaged tissue such as lung 10 , liver 11 , cholangiocyte 12 , CNS 13 , tendon 14 or sinusoidal endothelial cells 11 by promoting regeneration, managing inflammation and replacing damaged cells with functional/mature ones (without cell fusion). The level of maturation implies either a tissue replacement as epithelial cells [15][16][17][18][19][20][21] , or as mesenchymal cells by experiencing 1 Faculty of Bioscience and Technology for Food, Agriculture and Environment, University of Teramo, Teramo, Italy.…”
Section: Epithelial-mesenchymal Transition (Emt) Is a Complex Biologimentioning
confidence: 99%
“…Generally, HLCs derived from MSCs possess some mature and fetal hepatocyte features as has been shown by transcriptome and functional studies [102,103]. It should be noted that some differences are also reported depending on the origin of the MSC population (e.g., BM vs. umbilical cord vs. liver-derived MSCs; pediatric vs. adult MSCs) [87,95,104].…”
Section: Hepatic Differentiated Mesenchymal Stromal Cellsmentioning
confidence: 86%
“…For instance, Liu et al used a 14-day cytokine-based differentiation protocol to obtain HLCs from human AECs in 2D culture. Following grafting 2 × 10 6 of such AEC-HLCs in CCl 4 treated NOD-SCID mice, human cells were detected in the recipient liver (although the RI was not quantified) and liver injury was attenuated [104]. However, it remains to be addressed whether naïve AECs or in vitro differentiated AEC-HLCs are superior as an alternative cell source for alleviating liver failure and/or repopulating the host liver [114].…”
Section: Amniotic Epithelial Cellsmentioning
confidence: 99%
“…However, such concerns are not raised by the use of amnion epithelial cells [11] and, as it can be assumed, HLC obtained from them. Preclinical studies on mice [14,113] using HLC obtained from hAEC have shown, that their use in the treatment of liver failure in humans does not require the use of immunosuppressive treatment [13].…”
Section: Differentiation Of Amniotic Epithelial Cellsmentioning
confidence: 99%